Gully cavity identification through electrical resistivity tomography - Carrazza, Leonardo Paioli [UNESP]; Moreira, Cesar Augusto [UNESP]; Helene, Lívia Portes Innocenti [UNESP] (Sociedade Brasileira de Geofisica, 2016)
Chaotic urban expansion often leads to hazardous environmental consequences. The absense of rainwater outflow management, coupled with low cohesion in some terrains is a geotechnical threat for the population since it may lead to gully formation. Geophysics allows for the diagnostic of main gully erosion by products, such as piping phenomena, which generates natural underground cavities. The electrical resistivity contrast between soil and hollow cavities, favors the employment of the DC Resistivity method. This paper describes the use of electrical resistivity tomography in a gully investigation case in São Pedro County (SP) to detect cavities formed in a process known as internal erosion or piping. Six parallel lines of electrical imaging were used as a mean to collect electrical resistivity values. Eighty-four electrodes were placed; one meter apart from each other in each acquisition line, with a five-meter interval between each line according to the Wenner-Schlumberger array. The results showed a high resistivity signature, probably due to the absence of filling in the cavities. The lateral integration of the sections in an isovalue map regarding cavity depth occurency reveals the length and ramifications of the pipings in the internal portions of the terrain.
Keywords: Electrical resistivity; Electrical resistivity tomography; Geophysics; Piping